Assessing the implementation of computerized aided facility management (CAFM) in tertiary education institution in Selangor / Nor Izzati Mohd Rohaizad - Mohd Rohaizad, Nor Izzati (Faculty of Architecture, Planning and Surveying, 2013)
The function of Computerized Maintenance Facility Management (CAFM) is to support facilities management by information technology, for strategic facility management and to support operational system. However, from the problem statement shown CAFM needs considerable amount of time to complete the data depending on the size of the organizations. Apart from that, the applications of CAFM touch many parts of organizations and configuration and it’s an immense task. Therefore, the aim of this research is to enhance the implementation of CAFM in tertiary education. Three objectives of CAFM is to determine the current practice, challenge occurred and assist in tertiary education. Inspired by literature interview, this research conduct semi-structured interview in order to measure the implementation of CAFM in tertiary education. There are five universities involves that is Universiti Teknologi MARA (UiTM), Universiti Kebangsaan Malaysia (UKM), Universiti Malaya (UM), Universiti Tenaga Nasional (UNITEN), Universiti Industri Selangor (UNISEL) and Management and Science University (MSU).It involves Facility Manager as a respondent. The data is collected by using content analysis method. In this research, the analysis content has detailed information about all universities regarding the background information, company profile, types, module and variables of CAFM. From the analysis, we can recommend that research should be conducted for other respondent like lecturers, staffs, and vendors and can also carry out at other universities and organizations.